Effects of PPP1R1B (DARPP-32) Polymorphism on Feedback-Related Brain Potentials Across the Life Span - Hämmerer, Dorothea; Biele, Guido; Müller, Viktor; Thiele, Holger; Nürnberg, Peter; Heekeren, Hauke R.; Li, Shu-Chen (Frontiers in Psychology, 2013)
Maximizing gains during probabilistic reinforcement learning requires the updating of choice–outcome expectations at the time when the feedback about a specific choice or action is given. Extant theories and evidence suggest that dopaminergic modulation plays a crucial role in reinforcement learning and the updating of choice–outcome expectations. Furthermore, recently a positive component of the event-related potential (ERP) about 200 msec (P2) after feedback has been suggested to reflect such updating. The efficacy of dopaminergic modulation changes across the life span. However, to date investigations of age-related differences in feedback-related P2 during reinforcement learning are still scarce. The present study thus aims to investigate whether individual differences in the feedback-related P2 would be associated with polymorphic variations in a dopamine relevant gene PPP1R1B (also known as DARPP-32) and whether the genetic effect may differ between age groups. We observed larger P2 amplitudes in individuals carrying the genotype associated with higher dopamine receptor efficacy, i.e., A allele homozygotes of a single nucleotide polymorphism (rs907094) of the PPP1R1B gene. Moreover, this effect was more pronounced in children and older adults in comparison to adolescents and younger adults. Together, our findings indicate that polymorphic variations in a dopamine relevant gene are associated with individual differences in brain-evoked potentials of outcome updating and hint at the possibility that genotype effects on neurocognitive phenotypes may vary as a function of brain maturation and aging.